Intraoperative "Micro Breaks" With Targeted Stretching Enhance Surgeon Physical Function and Mental Focus: A Multicenter Cohort Study. Issue 2 (February 2017) - Park, Adrian E.; Zahiri, Hamid R.; Hallbeck, M. Susan; Augenstein, Vedra; Sutton, Erica; Yu, Denny; Lowndes, Bethany R.; Bingener, Juliane
Abstract : Objective: The aim of this study was to investigate the effect of intraoperative targeted stretching micro breaks (TSMBs) on the experienced pain and fatigue, physical functions, and mental focus of surgeons. Background: Surgeons are routinely subject to mental and physical stresses through the course of their work in the operating room. One of the factors most contributory to the shortening of a surgeon's career is work-related pain and its effects on patient safety and personal relationships. Methods: Surgeons and operating room staff from 4 medical centers rated pain/fatigue, physical, and mental performance using validated scales during 2 operative days: 1 day without implementing TSMB, the other including standardized (1.5 to 2 minutes) guided TSMB at appropriate 20 to 40-minute intervals throughout each case. Case type and duration were recorded as were surgeon pain data before and after each procedure and at the end of the surgical day. Individual body part pre/postdiscomfort difference was modeled, controlling for clinical center. Random coefficient mixed models accounted for surgeon variability. Results: Sixty-six participants (69% men, 31% women; mean 47 years) completed 193 "non-TSMB" and 148 "TSMB" procedures. Forty-seven percent of surgeons were concerned that musculoskeletal pain may shorten their career. TSMB improved surgeon postprocedure pain scores in the neck, lower back, shoulders, upper back, wrists/hands, knees, and ankles. Operative duration did not differ ( P > 0.05). Improved pain scores with TSMB were statistically equivalent ( P > 0.05) for laparoscopic and open procedures. Surgeons perceived improvements in physical performance (57%) and mental focus (38%); 87% of respondents planned to continue TSMB. Conclusions: Many surgeons are concerned about career-ending or limiting musculoskeletal pain. Intraoperative TSMB may represent a practical, effective means to reduce surgeon pain, enhance performance, and increase mental focus without extending operative time. Abstract : Supplemental Digital Content is available in the text